Gut microbiota diversity is altered in a sex-dependent manner in Shank3B heterozygote mice - Turner, Finley; Williams, Mykle; Gregoretti, Sophie; Bielamowicz, Delano; Roach, Kylie; Gehner, Lil; Kunnatha, Anjali; Phillips, Shekinah; Hagel, Rosie; Harshman, Rebecca; Vargo, Erika; Dutton, Stacey B. B.; et al. (Frontiers in Microbiomes, 2025)
The gut-brain axis is a dynamic interface that has been implicated in the pathogenesis and severity of various neurodevelopmental disorders such as schizophrenia (SZ) and autism spectrum disorders (ASD). Also implicated in ASD and SZ, SHANK3B is a critical gene for postsynaptic protein scaffolding at excitatory synapses. Shank3B knockout mice not only exhibit ASD-like behaviors but demonstrate altered gastrointestinal epithelium morphology and fecal microbiota composition. Utilizing Shank3B heterozygote mice to better reflect the clinical presentation of ASD, we sequenced the gut microbiome from the small intestine of 12-week-old wild type Shank3B+/+ or Shank3B+/- mice in a sex-dependent manner, analyzing bacterial phyla, classes, orders, families, genera, and species. Firmicutes emerged as the dominant phylum in Shank3B+/- mice and Bacilli as the dominant class, with Lactobacillales as the dominant order. The dominant family is Lactobacillaceae. The Shank3B+/- males but not the Shank3B+/- females show an increase in Staphylococcaceae and Erysipelotricaceae. Our results indicate increased biodiversity in Shank3B+/- males and reduced biodiversity in Shank3B+/- females compared to wild-type controls. Altogether, this data reveals sex-specific microbial signatures that may contribute to the pathogenesis of ASD thus providing potential therapeutics that target gut microbiota in neurodevelopmental disorders.